Analysis of the adjuvant effect of recombinant Leishmania infantum Hsp83 protein as a tool for vaccination - Echeverria, Pablo Christian (2001)
The properties of Leishmania infantum hsp83 (LiHsp83) to elicit an immune response against a fused reporter antigen, maltose binding protein (MBP), was studied. CF1 mice were immunized with different purified recombinant proteins: MBP, LiHsp83 and MBP fused to LiHsp83 (MBP-LiHsp83). Serum samples were obtained at days 0, 21, 28, 60, 90, 120 and 150 post-immunization. MBP-LiHsp83 fusion protein elicited a strong humoral response against MBP, higher than that one obtained in mice immunized with MBP alone or MBP mixed with LiHsp83, showing the secretion of both anti-MBP IgG2a and IgG1 isotypes (IgG2a/IgG1 ratio: 2:1). This response was specific for recombinant proteins and was maintained for at least 150 days, whereas the reactivity in mice immunized with MBP alone dissapeared at day 90. After in vitro stimulation with MBP, spleen cells from MBP-LiHsp83 immunized mice showed higher proliferation indices and produced higher secretion of IFN-γ than spleen cells from either control or MBP-immunized mice. In all groups of mice IL-4 was undetectable. Thus we consider that LiHsp83 may be a promising candidate to be used as carrier of fused antigens for adjuvant-free vaccination. © 2001 Elsevier Science B.V.